Correlates of recent HIV testing among substance-using men who have sex with men. (May 2017) - Rowe, Christopher; Matheson, Tim; Das, Moupali; DeMicco, Erin; Herbst, Jeffrey H; Coffin, Phillip O; Santos, Glenn-Milo
Men who have sex with men are disproportionately impacted by HIV and substance use is a key driver of HIV risk and transmission among this population. We conducted a cross-sectional survey of 3242 HIV-negative substance-using men who have sex with men aged 18 + in the San Francisco Bay Area from March 2009 to May 2012. Demographic characteristics and sexual risk and substance use behaviors in the last six months were collected using structured telephone questionnaires. We used multivariable logistic regression to identify independent demographic and behavioral predictors of recent HIV testing. In all, 65% reported having an HIV test in the last six months. In multivariable analysis, increasing age (aOR = 0.87, 95% CI = 0.84–0.90) and drinking alcohol (<1 drink/day: 0.65, 0.46–0.92; 2–3 drinks/day: 0.64, 0.45–0.91; 4 + drinks/day: 0.52, 0.35–0.78) were negatively associated with recent HIV testing. Having two or more condomless anal intercourse partners (2.17, 1.69–2.79) was positively associated with having a recent HIV test, whereas condomless anal intercourse with serodiscordant partners was not significantly associated with testing. Older men who have sex with men and those who drink alcohol may benefit from specific targeting in efforts to expand HIV testing. Inherently riskier discordant serostatus of partners is not as significant a motivator of HIV testing as condomless anal intercourse in general.